Aerospace and Mechanical Engineering Selected, peer reviewed papers from the 2014 Conference on Aerospace and Mechanical Engineering (AME 2014), April 13-14, 2014, Bangkok, Thailand (Trans Tech Publications Ltd, 2014)
Collection of selected, peer reviewed papers from the 2014 Conference on Aerospace and Mechanical Engineering (AME 2014), April 13-14, 2014, Bangkok, Thailand. Volume is indexed by Thomson Reuters CPCI-S (WoS).The 45 papers are grouped as follows: Chapter 1: Materials Science and Materials Processing Technology, Chapter 2: Aerospace and Mechanical Engineering, Applied Mechanics, Chapter 3: Computation Methods and Information Technologies Keyword: Materials Science and Materials Processing Technology; Aerospace and Mechanical Engineering, Applied Mechanics; Computation Methods and Information Technologies